Fabrication process of palm empty fruit brunches reinforced with box waste coated super hydrophobic for shoe pad application - Marsi, Noraini; Thana Singam, Rupashinii; Chow, Li Kien; Mohd Rus, Anika Zafiah; Darlis, Norfrizalidris; Masrol, Shaiful Rizal; Kasmin, Ashari (Penerbit UTHM, 2020)
The shoe manufacturing process goes back to 1844 when Charles Goodyear made a breakthrough after years of experimentation. The researcher used a process and called as vulcanization to heat natural rubber in order to mix it with sulfur and a concoction that helped create the type of rubber used in shoe soles today...